Perancangan Sistem Informasi Perpustakaan Negeri Pelangi Berbasis Website - Fenilinas Adi Artanto (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2023)
Technological developments make the need for appropriate technology a main thing in public services. Likewise with the Pelangi State Library which is located in Podosugih, Pekalongan City. Currently the Pelangi State Library needs a Library Information System that can be used as a means of borrowing and borrowing books at the library. A system based on a website to make it easier for users to access access anywhere. A library information system that has 2 actors, namely library staff or admin who can add members and also list books. Apart from admins, there are also user actors, namely library book borrowers who can fill in their own lists of borrowing and returning books independently. Therefore, a library information system was created using Unifield Modeling Language (UML) design. From the existing design, a Rainbow State Library Information System has been designed. The Information System has also been tested using black box testing and shows that the system built is in accordance with the system design that has been created.